2014
DOI: 10.1097/mjt.0b013e3182491e14
|View full text |Cite
|
Sign up to set email alerts
|

Case Report Series of Left Atrial Thrombus Formation in Patients on Dabigatran Therapy

Abstract: Dabigatran etexilate mesylate, a direct thrombin inhibitor, has been approved in the United States as an alternative to warfarin for the prevention of stroke and systemic thromboembolism in patients with nonvalvular atrial fibrillation. The authors report 2 cases of development of large left atrial thrombi and unfortunate occurrence of thromboembolic events in patients with chronic atrial fibrillation, despite these patients being compliant with recommended dabigatran therapy. The authors postulate that certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has also been used in patients with atrial fibrillation who had documented left atrial thrombus, proving its role in resolution of thrombus [ 4 , 5 ]. However, left atrial thrombus formation on dabigatran therapy as in our case has been reported in 3 other cases in the literature till date [ 6 , 7 ]. Sharma et al [ 6 ] recently reported two cases of left atrial thrombus formation on dabigatran therapy for chronic atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It has also been used in patients with atrial fibrillation who had documented left atrial thrombus, proving its role in resolution of thrombus [ 4 , 5 ]. However, left atrial thrombus formation on dabigatran therapy as in our case has been reported in 3 other cases in the literature till date [ 6 , 7 ]. Sharma et al [ 6 ] recently reported two cases of left atrial thrombus formation on dabigatran therapy for chronic atrial fibrillation.…”
Section: Discussionmentioning
confidence: 67%
“…However, left atrial thrombus formation on dabigatran therapy as in our case has been reported in 3 other cases in the literature till date [ 6 , 7 ]. Sharma et al [ 6 ] recently reported two cases of left atrial thrombus formation on dabigatran therapy for chronic atrial fibrillation. One of the patients had lung cancer which could have contributed to additional risk of thrombosis, while the other patient was similar to our case.…”
Section: Discussionmentioning
confidence: 67%
“…However, this therapeutic advantage of dabigatran is not observed in the treatment of left atrial appendage thrombus, with many reports showing variable responses from increasing the clot size to complete clot resolution 19–22…”
Section: Discussionmentioning
confidence: 99%
“…Luis et al ( 2013 ) firstly reported the images which demonstrated the documented case of thrombosis in atrial fibrillation with coexistent valvular heart disease after 4 months anticoagulation with dabigatran. Sharma et al ( 2014 ) report 2 cases of development of large left atrial thrombus in spite of the continuous treatment with dabigatran. Shah et al ( 2015 ) reported another patient with thrombus formation in the left atrium.…”
Section: Discussionmentioning
confidence: 99%